Use of Methods of Multidimensional Grouping for Statistical Analysis of Energy Consumption at Regional Level - L. L. Poltavets (Статистика України, 2017)
Effective energy consumption at macro- or mesolevel is an important factor of economic development Consumption of energy resources (coal, gas and electricity in case of this study) in Ukrainian regions is uneven, being dependent on factors like share of industrial and agricultural output in regional value added, average income per capita in a region, share of out-dated industrial technologies in a region. In view of this, the objective of the study is to make clustering of Ukrainian regions by coal, gas and electricity consumption. The analysis rests on testing the following hypothesis: due to geographic and economic differences of the regions, the consumption of the above resources is distributed by them unevenly, which leads to the occurrence of homogenous groups of regions by measures of consumption of these resources.